Evolution and functional classification of vertebrate gene deserts - Ovcharenko, Ivan; Loots, Gabriela G.; Nobrega, Marcelo A.; Hardison, Ross C.; Miller, Webb; Stubbs, Lisa (Genome Research, 2005)
Large tracts of the human genome, known as gene deserts, are devoid of protein-coding genes. Dichotomy in their level of conservation with chicken separates these regions into two distinct categories, stable and variable. The separation is not caused by differences in rates of neutral evolution but instead appears to be related to different biological functions of stable and variable gene deserts in the human genome. Gene Ontology categories of the adjacent genes are strongly biased toward transcriptional regulation and development for the stable gene deserts, and toward distinctively different functions for the variable gene deserts. Stable gene deserts resist chromosomal rearrangements and appear to harbor multiple distant regulatory elements physically linked to their neighboring genes, with the linearity of conservation invariant throughout vertebrate evolution.